1995
DOI: 10.1007/bf01839301
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ageing on muscarinic receptors, β-adrenoceptors and adenylate cyclase activity in the bovine lung

Abstract: Muscarinic and beta-adrenoceptors were identified in airway epithelium, smooth muscle and lung parenchyma from Holstein-Friesian calves and cows and were characterized with [3H]quinuclidinyl benzilate and [3H]dihydroalprenolol, respectively. The muscarinic receptor density in the smooth muscle of cows (Bmax = 4803 +/- 245 fmol/mg protein) was 33% greater (p < 0.01) than in calves. Low receptor numbers were detected in the epithelium and parenchyma. In both calves and cows, the density of epithelial beta-adreno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…In fact, the density of muscarinic receptors in the equine peripheral lung (22 fmol/mg protein) was much lower (3-10 times) than reported B max values for human, pig, bovine, rabbit, rat or guinea pig peripheral lung tissue (Bloom et al, 1988;Cheng and Townley, 1982;Gies et al, 1989;Haddad et al, 1994). In addition, in conducting airways, the number of muscarinic receptors was higher in bovines (Cheng and Townley, 1982;Roets and Burvenich, 1995), pigs (Yang et al, 1986) and humans (van Koppen et al, 1985) than in the horse. However, in these species, receptor characterization was done either in isolated smooth-muscle preparations or in membranes of isolated epithelial cells, in which the number of binding sites is significantly lower (Yang et al, 1986;Roets and Burvenich, 1995).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In fact, the density of muscarinic receptors in the equine peripheral lung (22 fmol/mg protein) was much lower (3-10 times) than reported B max values for human, pig, bovine, rabbit, rat or guinea pig peripheral lung tissue (Bloom et al, 1988;Cheng and Townley, 1982;Gies et al, 1989;Haddad et al, 1994). In addition, in conducting airways, the number of muscarinic receptors was higher in bovines (Cheng and Townley, 1982;Roets and Burvenich, 1995), pigs (Yang et al, 1986) and humans (van Koppen et al, 1985) than in the horse. However, in these species, receptor characterization was done either in isolated smooth-muscle preparations or in membranes of isolated epithelial cells, in which the number of binding sites is significantly lower (Yang et al, 1986;Roets and Burvenich, 1995).…”
Section: Discussioncontrasting
confidence: 48%
“…In addition, in conducting airways, the number of muscarinic receptors was higher in bovines (Cheng and Townley, 1982;Roets and Burvenich, 1995), pigs (Yang et al, 1986) and humans (van Koppen et al, 1985) than in the horse. However, in these species, receptor characterization was done either in isolated smooth-muscle preparations or in membranes of isolated epithelial cells, in which the number of binding sites is significantly lower (Yang et al, 1986;Roets and Burvenich, 1995). Moreover, in isolated equine tracheal epithelial cells, Törneke and colleagues (2002) found a lower number of muscarinic receptors, suggesting the presence of more receptors in the tracheal smooth muscle (present study) than in epithelial cells.…”
Section: Discussionmentioning
confidence: 94%
“…Further, age-related changes in the effectiveness of the βAR agonists isoproterenol and fenoterol in both guinea pig and rat isolated tracheal smooth muscle have been reported [100]. An age-associated decrease in βARs has also been described in bovine airways: the quantity of βARs in tracheal epithelium and smooth muscle in cows was 37% and 35% lower, respectively, than in calves [101]. Corroborating these findings, an age-linked reduction in the responsiveness of human subjects to specific β 2 AR agonists has been reported [102].…”
Section: Introductionmentioning
confidence: 99%
“…Availability of functional receptors will directly affect the concentration of agonist-receptor complexes, thereby the degree of elicited response. Previously, a decrease (Rothberg et al, 1987), increase (Roets and Burvenich, 1995), or no change (Haxhiu-Poskurica et al, 1993) in the total density of muscarinic receptors with maturation has been reported using bovine or piglet trachea. Therefore previous studies have been inconclusive.…”
Section: Discussionmentioning
confidence: 95%